Awareness and Use of Post-exposure Prophylaxis for HIV Prevention Among Men Who Have Sex With Men: A Systematic Review and Meta-Analysis - Jin, Junyan; Sun, Runsong; Mu, Tingting; Jiang, Taiyi; Dai, Lili; Lu, Hongyan; Ren, Xianlong; Chen, Jing; Ye, Jingrong; Sun, Lijun; Wu, Hao; Zhang, Tong; et al. (Frontiers in Medicine, 2022)
Background: The use of post-exposure prophylaxis (PEP) is effective in reducing HIV risk, but it is underused by men who have sex with men (MSM) due to certain psychological and sociostructural factors. This article assessed the awareness and use of PEP among MSM in an effort to increase the visibility and uptake of PEP among at-risk populations. Methods: We conducted a systematic literature search of the PubMed, Web of Science, PsycINFO, and Google Scholar electronic databases. Studies were screened for inclusion, and relevant data were abstracted, assessed for bias, and synthesized. Pooled effect estimates were calculated using random effects meta-analysis, meta-regression and subgroup analysis, and a qualitative review and risk of bias assessment were performed (PROSPERO, CRD42019123815). Results: Twenty eligible studies involving 12,579 MSM were included in the meta-analysis. The pooled estimate of the proportions of MSM who were aware of PEP was modest at 59.9% (95% CI: 50.5~68.7) and that of MSM who previously used PEP was very low at 4.9% (95% CI: 2.4~9.8). PEP awareness showed no clear change over time, while PEP use significantly changed over time. Multiple factors affected awareness, including educational attainment, race/ethnicity, levels of HIV stigma, access to condoms, and so on. Many factors could potentially impede or facilitate the use of PEP, such as income, lack of PEP information, and partnership. Conclusion: We observed that PEP is an underused HIV prevention strategy among MSM and that once MSM become aware of PEP, the majority are willing to use it if they are supported appropriately in terms of a range of individual, social, and structural barriers.